Democracy Distorted –Deepfakes as Political Weapons - Rakipi, Gjon; Yousefi, Yasaman; Caltagirone, Calogero; Tumminelli, Angelo; McIntyre, Andrew; Dimitrova, Aseniya (Deepfakes, Democracy, and the Ethics of Synthetic Media: A Synthesis of the SOLARIS Project, 2026)
Affordable generative AI allows actors to produce and amplify deepfakes instantly, outpacing verification efforts. Drawing on Young’s (2011) distinction between isolated harms and structural injustice, this chapter identifies synthetic media as a structural threat to democracy that collapses the evidentiary foundations of public reason. We examine how deepfakes weaponize information ecosystems, using European and U.S. case studies to demonstrate their specific deployment against women and minority candidates. Methodologically, we analyse recent disinformation incidents through the lenses of epistemic injustice and deliberative democracy. We argue that deepfakes signal a deeper vulnerability where truth becomes malleable and public trust erodes. The chapter concludes that safeguarding democratic life requires not only legal and technical fixes, but a normative reorientation toward truthfulness and accountability.